2014
DOI: 10.1007/s10067-014-2633-z
|View full text |Cite
|
Sign up to set email alerts
|

Takayasu’s arteritis in Arabs

Abstract: The objective of this study was to describe epidemiological and clinical features of Takayasu's arteritis (TA) among Arab populations and to compare it to other populations. We conducted a systematic review of reports about TA from Arab countries published in English and French until 2013. All published papers were reviewed including original research and case reports. There were 197 patients (176 females) reported in 28 publications that comprised 8 original research publications (with a total of 163 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…A systematic review collected only 197 patients from 7 Arab countries with a population of approximately 80 million, demonstrating a low prevalence [24]. The demographical and clinical findings of TAK in Arabs is reported to be similar to other series, with the course of the disease "quite stable'' in about 50% of patients and the overall mortality is low during 5.4 years of follow-up.…”
Section: Prevalence and Ethnicitysupporting
confidence: 52%
“…A systematic review collected only 197 patients from 7 Arab countries with a population of approximately 80 million, demonstrating a low prevalence [24]. The demographical and clinical findings of TAK in Arabs is reported to be similar to other series, with the course of the disease "quite stable'' in about 50% of patients and the overall mortality is low during 5.4 years of follow-up.…”
Section: Prevalence and Ethnicitysupporting
confidence: 52%
“…In Western Australia, per million inhabitants the annual incidence and prevalence was 0.3 and 3.2 for Caucasians and 1.1 and 15 for Asians [13]. In Arabs, the demographical and clinical findings of TA were reported to be similar to that reported from different parts of the world [14].…”
Section: Introductionmentioning
confidence: 53%
“…10 In 2014, a review in Arab populations of seven countries reported demographic findings comparable with those in other parts of the world. [11][12][13][14]…”
Section: Epidemiologymentioning
confidence: 99%
“…In 2012, four Italian patients with active LVV (two with GCA and two with TA), treated with TCZ, showed a satisfactory clinical and laboratory response, with significant improvements in PET/CT findings, without serious adverse events. 61 In 2017, a single-center prospective study analyzed the efficacy and safety of TCZ in 16 Chinese TA patients (15 patients with previous conventional immune suppressants); three patients withdrew TCZ after one infusion due to unbearable neck pain; the other 13 patients were treated for a median of 13 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) months with reduction of ESR, CRP, and mural thickness of common carotid artery and subclavian artery. 62 The favorable outcome of B-cell depletion therapy through rituximab treatment in refractory TA was reported by Hoyer in 2012 (three subjects) and Caltran et al in 2014 (two subjects).…”
Section: Conventional Immunosuppressant Therapymentioning
confidence: 99%